Farmers’ Perceptions Regarding the use of Botswana’s Tsa Temo Thuo Television Programme - K, Gababolokwe; K, Hulela (Asian Journal of Agriculture and Rural Development, 2014)
The purpose of the study was to examine farmers’ perceptions about the usefulness of the Tsa Temo Thuo agricultural programmes broadcasted every Monday of the week on the Botswana Television between 7:30 and 8:00 pm for farmers. A questionnaire was used to gather data from 36 farmers with different agricultural backgrounds in the Boteti sub-district regarding the effectiveness of the programme in disseminating information. A simple random sampling technique was used to get the 36 farmers from the list of 40 farmers. The results showed that the farmers saw the programme as relevant for their farming services but voiced that the programme be frequently reviewed to ensure emerging issues were integrated. The results also revealed that factors such as farming environment (Mean = 4.36; SD = .49); access to television programme (Mean = 4.22; SD = .59) and ignorance about farming issues (Mean = 3.36; SD = 1.05) were perceived as useful. However, this being a case study, a similar study should be conducted nationwide to ascertain and compare the perceived effectiveness of the television programme.